Association between hypertension and self-perception of health status: Findings from a decade population-based survey in Spanish adults - Jesús Martín-Fernández; Tamara Alonso-Safont; Elena Polentinos-Castro; Gemma Rodríguez-Martínez; Mª Isabel González-Anglada; Amaia Bilbao-González; Isabel del-Cura-González (PLoS ONE, 2025)
Objective This study, conducted in the community setting, aimed to assess and discuss how a diagnosis of arterial hypertension affects self-perceived health status, examining the association with potential explanatory factors and comparing its impact with that of other chronic conditions. Methods Cross-sectional observational study using the 2011–2012 and 2017 Spanish National Health Surveys and the 2020 European Health Interview Survey for Spain as data sources. Health perception was categorised as very good, good, fair, bad, or very bad. The independent variables recorded demographic, social, clinical, and lifestyle information. The associations between variables were evaluated via a generalisation of an ordered logit model. Results A total of 66,168 subjects were included (21,007 in 2011, 23,089 in 2017, and 22,072 in 2020), 21.6% of whom were diagnosed with hypertension, 51.3% were women, and the average age was 48.24 (18.89) years. Around one in five people in the general population reported a “very good” health status. The probability of reporting a “very good” health condition decreased with a diagnosis of hypertension (6.2%; CI 95%: 3.1–9.3%) and hypertensive medication (4.5%; CI 95%: 1.8–7.3%). Such associations were independent of age, gender, social group, other chronic conditions or limitations, or various lifestyle habits. In contrast, no association was found with reporting a “bad” or “very bad” health status. Conclusion Being diagnosed with hypertension and prescription of antihypertensive medication are associated with a lower probability of reporting a “very good” health status, irrespective of other comorbidities or complications related to the diagnosis.